A genome-wide association study on confection consumption in a Japanese population: the Japan Multi-Institutional Collaborative Cohort Study. Issue 12 (28th December 2021) - Suzuki, Taro; Nakamura, Yasuyuki; Doi, Yukio; Narita, Akira; Shimizu, Atsushi; Imaeda, Nahomi; Goto, Chiho; Matsui, Kenji; Kadota, Aya; Miura, Katsuyuki; Nakatochi, Masahiro; Tanaka, Keitaro; et al.
Abstract: Differences in individual eating habits may be influenced by genetic factors, in addition to cultural, social or environmental factors. Previous studies suggested that genetic variants within sweet taste receptor genes family were associated with sweet taste perception and the intake of sweet foods. The aim of this study was to conduct a genome-wide association study (GWAS) to find genetic variations that affect confection consumption in a Japanese population. We analysed GWAS data on confection consumption using 14 073 participants from the Japan Multi-Institutional Collaborative Cohort study. We used a semi-quantitative FFQ to estimate food intake that was validated previously. Association of the imputed variants with confection consumption was performed by linear regression analysis with adjustments for age, sex, total energy intake and principal component analysis components 1–3. Furthermore, the analysis was repeated adjusting for alcohol intake (g/d) in addition to the above-described variables. We found 418 SNP located in 12q24 that were associated with confection consumption. SNP with the ten lowest P -values were located on nine genes including at the BRAP, ACAD10 and aldehyde dehydrogenase 2 regions on 12q24.12-13. After adjustment for alcohol intake, no variant was associated with confections intake with genome-wide significance. In conclusion, we found a significant number of SNP located on 12q24 genes that were associated with confections intake before adjustment for alcohol intake. However, all of them lost statistical significance after adjustment for alcohol intake.